2021
DOI: 10.1021/acscatal.1c00242
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Metal-Free α-C(sp3)–H Carbamoylation of Saturated Aza-Heterocycles via Rationally Designed Organic Photocatalyst

Abstract: Herein, we report a general strategy for the rational design of an efficient organic photocatalyst, and we describe a robust method for the direct C(sp 3 )−H carbamoylation of saturated aza-heterocycles under mild conditions by using a naphthalimide (NI)-based organic photocatalyst. This protocol provides a concise and practical approach for the rapid installation of a valuable amide bond onto pharmaceutically useful saturated aza-heterocycles to access a wide range of cyclic α-amino amides. A series of mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 83 publications
0
25
0
Order By: Relevance
“…In addition, the ortho -position substituted N -phenylmorpholines ( 7a–9a ) were slightly hindered to deliver the desired products with 51–67% yields due to steric hindrance. 57 Apart from morpholines, substituted piperazine ( 12a ) was also investigated, and only 40% of the corresponding product ( 12b ) was observed.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the ortho -position substituted N -phenylmorpholines ( 7a–9a ) were slightly hindered to deliver the desired products with 51–67% yields due to steric hindrance. 57 Apart from morpholines, substituted piperazine ( 12a ) was also investigated, and only 40% of the corresponding product ( 12b ) was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Xu and co-workers designed a novel naphthalimide based organic photocatalyst (Cz-NI) for the direct C(sp 3 )–H carbamoylation of saturated aza-heterocycles 207a by oxidative Ugi reaction under mild conditions (Scheme 207). 269 A high primary kinetic isotope effect ( k H / k D = 3.3) indicated that the C(sp 3 )–H bond cleavage was the rate limiting step of this carbamoylation reaction. After thorough experiments, it was also confirmed that the oxygen atom of the carbonyl group in the amide product came from the water generated by the photocatalytic process from pentafluoro nitrobenzene (PFNB).…”
Section: Metal Free Photo Induced C–h Functionalisationmentioning
confidence: 99%
“…The development of metal-free methods for the efficient synthesis of valuable organic compounds is an exciting area of research, due to their capability to produce non-toxic metal-free drugs and medicinally important compounds. [1][2][3][4] In this regard, molecular iodine was used as an efficient catalyst in the synthesis of many heterocyclic compounds via multicomponent reactions. [5][6][7][8] Benzoxazoles are one of the important classes of nitrogen-containing heterocycles with extensive utilization especially in medicinal chemistry.…”
Section: Introductionmentioning
confidence: 99%